OPTIMALISASI KEMAMPUAN PEMECAHAN MASALAH MELALUI MODEL PEMBELAJARAN CIRC BERBANTUAN MEDIA BONUCA - Cawla, Dita; Virdinarti Putra, Lisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the optimization of students' problem-solving abilities through the application of the Integrated Cooperative Reading and Writing (CIRC) learning model assisted by BONUCA (Board Number Card) learning media. This study was conducted on fourth-grade students of SDN Langensari 04 using quantitative research methods and a quasi-experimental approach. There were two research samples, namely class IV B with 18 students as the experimental class and class IV A with 21 students as the control class. Data collection techniques used in this study were test and non-test techniques. The test techniques used were pretest and posttest, while non-test techniques were observation, questionnaires, and documentation. Data analysis techniques used in this study were normality test, homogeneity test, independent sample t-test, and simple linear regression. The results of the study showed: 1) there were differences in problem-solving abilities through the use of the CIRC model assisted by BONUCA media with the results of the Independent Sample t-test showing a t value = -1.852 with df = 37 and a significance value (2-tailed) = 0.002 <0.05. 2) There is an influence of the CIRC model assisted by BONUCA media on students' problem-solving abilities, with a significance value (Sig.) of 0.034 < 0.05.